Pattern of prefrontal cortical activation and network revealed by task-based and resting-state fNIRS in Parkinson’s disease’s patients with overactive bladder symptoms - Hou, Miaomiao; Mao, Xiaowei; Wei, Yarong; Wang, Jiali; Zhang, Yu; Qi, Chen; Song, Lu; Wan, Ying; Liu, Zhihua; Gan, Jing; Liu, Zhenguo (Frontiers in Neuroscience, 2023)
Background Overactive bladder (OAB) symptoms are common in Parkinson’s disease (PD), and negatively contribute to the quality of life (QoL) of patients. To explore the underlying pathophysiological mechanism, we investigated the correlation between the prefrontal cortex (PFC) function and OAB symptoms in PD patients. Methods One hundred fifty-five idiopathic PD patients were recruited and classified either as PD-OAB or PD-NOAB candidates based on their corresponding OAB symptom scores (OABSS). A linear regression analysis identified a correlative connection of cognitive domains. Then cortical activation during the performance of the verbal fluency test (VFT) and brain connectivity during resting state were conducted by functional near-infrared spectroscopy (fNIRS) for 10 patients in each group to investigate their frontal cortical activation and network pattern. Results In cognitive function analysis, a higher OABS score was significantly correlated with a lower FAB score, MoCA total score, and sub-scores of visuospatial/executive, attention, and orientation as well. In the fNIRS study, the PD-OAB group exhibited significant activations in 5 channels over the left hemisphere, 4 over the right hemisphere, and 1 in the median during the VFT process. In contrast, only 1 channel over the right hemisphere showed significant activation in the PD-NOAB group. The PD-OAB group revealed hyperactivation, particularly in certain channel in the left dorsolateral prefrontal cortex (DLPFC), compared with PD-NOAB (FDR P < 0.05). In the resting state, there was a significant increase of the resting state functional connectivity (RSFC) strength between the bilateral Broca area, left frontopolar area (FPA-L) and right Broca’s area (Broca-R), between the FPA and Broca’s area if merging the bilateral regions of interest (ROI), and also between the two hemispheres in the PD-OAB group. The Spearman’s correlation confirmed that the OABS scores were positively correlated with RSFC strength between the bilateral Broca area, FPA-L and Broca-R, between the FPA and Broca area if merging the bilateral ROI. Conclusion In this PD cohort, OAB was related to decreased PFC functions, with particularly hyperactivated left DLPFC during VTF and an enhanced neural connectivity between the two hemispheres in the resting state as observed by fNIRS imaging.